Enhancing Wound Care Practices for Patients with Comorbidities: Evidence from Hospitals in the 5th District of Camarines Sur, Philippines - Michael N. Orbon; Cyril B. Romero; Jane M. Tagum-Briones (Jurnal Genesis Indonesia, 2026)
This study examines wound care practices among healthcare providers managing patients with comorbidities in hospitals in the 5th District of Camarines Sur, Philippines. Using a descriptive-evaluative design, data were collected from 147 nurses through structured questionnaires and analyzed using frequency, percentage, weighted mean, and chi-square tests. Findings indicate that wound care practices are generally “very much practiced,” particularly in wound cleaning, dressing, documentation, and patient education. However, gaps remain in the use of standardized assessment tools and educational resources. Statistical analysis revealed that age, educational attainment, area of assignment, length of service, and training significantly influence wound care practices, while sex does not. Common challenges include delayed wound healing, infection risks, and patient noncompliance. The study proposes a comprehensive wound care management program integrating early detection, multidisciplinary collaboration, and continuous professional development. These findings highlight the need for standardized protocols and capacity-building initiatives to improve patient outcomes in complex clinical settings.